TANGGUNG JAWAB MORAL DAN TANGGUNG JAWAB PROFESIONAL ADVOKAT DALAM PEMBERIAN BANTUAN HUKUM - Laksono, Alam Suryo; Gettari, Tri Tahmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This article explores the moral and professional responsibilities of lawyers in providing legal aid, using a conceptual and theoretical approach. Moral responsibility is rooted in normative ethics and distributive justice, emphasizing the lawyer’s role as an agent of justice for marginalized communities. Professional responsibility is framed within legal regulations and ethical codes. Employing Rawls’ theory of justice, Bayles’ professional ethics, and responsive-progressive legal theory, this study addresses challenges, integration strategies, and the urgency of ethical reorientation in legal practice. The reinforcement of pro bono ethics is proposed as a foundational element to expand access to justice. The findings highlight that synergy between morality and professionalism is essential in developing equitable, humanistic, and sustainable legal aid practices.Keywords: Lawyer, Moral Responsibility, Professional Responsibility, Legal Aid, Professional Ethics